PENGARUH KUALITAS PELAYANAN, KETEPATAN WAKTU PENGIRIMAN DAN FASILITAS TERHADAP KEPUASAN PELANGGAN EKSPEDISI LION PARCEL DI BATAM - Tania, Tania; Raymond, Raymond (LPPM Universitas Putera Batam, 2021)
The needs to develop product shipment services in this modern era where many people open online businesses is needed. The purposes of this studies is finds outs the influenced of service qualities, delivery speed, and facilities at costumer’s satisfaction of Lion Parcel expedition. The variables are Service Quality (X1), Delivery Speed (X2), and Facilities(X3) to Costumer’s Satisfaction(Y). The methods use in this studies are statistical analysis method consisting multiples linears regressions analys i.e. determinationed analys, significant hypothesis testing consisting the T test and F test. The analysis concludes that (1)The services qualities had significants influenced at costumer’s satisfactions because the significances value is 0,023 less than 0,05 and the T value for service quality is 2,315 greater than T table(1,984). (2) The delivery speed has significants influences at costumer’s satisfactions because the significances valued are 0,034 less than 0,05 and the T value for the delivery speed is 2,149 greater than T table (1,984). (3) The facilities has significant influence on costumer’s satisfaction because the significance value is 0,05 and the T value for the facilities is 5,193 greater than T table(1,984). (4) Service quality, delivery speed, and facilities, has significant influence on costumer's satisfaction because the significance value is 0,05 and the F value for costumer’s satisfaction, delivery speed and facilities is 171,810 greater than the F table of 2,70.